Therapeutic monitoring of valproic acid - benefits and problems - Agnieszka Małgorzata Cios; Anna Wesołowska; Elżbieta Szczygieł-Pilut; Anna Zajączkowska-Dutkiewicz; Łukasz Hońdo; Iana Kachalka (Polish Pharmaceutical Society, 2021)
The anticonvulsant properties of valproic acid (VPA), a branched short-chain fatty acid, were serendipitously discovered in 1963. Since then, therapeutic roles of VPA have increased to include bipolar disorder and migraine prophylaxis, and have more recently been proposed in cancer, Alzheimer's disease, and HIV treatment. Overall, most patients with epilepsy are optimally treated with serum VPA concentrations of 50-100 mg/l. The unpredictable relationship between dose and VPA concentration supports the need to individualize and maintain therapy using therapeutic drug monitoring (TDM). TDM has been used as a tool to optimize treatment of epilepsy for almost 50 years, and while VPA evidence for its usefulness in improving clinical outcome is scarce, TDM continues to play a role in epilepsy management for reasons: (1)physiological changes due to aging, pregnancy, nutritional status, drug interactions, and comorbidities (ie, those involving liver and kidney function) can affect the pharmacokinetics of this drug; (2)treatment is prophylactic and seizures may occur at irregular intervals; (3)signs of toxicity may be insidious and difficult to interpret, especially if there is associated mental handicap or treatment with multiple antiepileptic drugs (AEDs). The chronic, sometimes lifelong therapy makes it particularly important to monitor treatment to reduce long-term adverse effects. These arguments for TDM are valid regardless of the AED involved. This article discusses the basic pharmacokinetic characteristics of conventional anti-epileptic drugs such as VPA. We summarized current clinical practice using TDM. We described the relationships between serum VPA concentration, clinical effect, and adverse drug reactions as well as the reference concentration range. It concluded that a therapeutic decision should not ultimately be based on serum VPA levels alone; other important factors should be considered including an interview with a patient and his medical history, clinical laboratory and pharmacogenetic data, and very importantly, the patient's individual therapeutic concentration of VPA in serum.